(The Effect of Stove Change Design and The Specific Gravity Briquette Bamboo Charcoal to Increasing of Heating efficiency) - H.G Pohan; Priyo Waspodo; Yang Yang Setiawan (Balai Besar Industri Agro, 2009)
Experiment on the use of modified anglo (rural type of stove) and density of bamboo charcoal briquette of Andong (Gigantochloa pseudoarundinaceae) and Petung (Denrocalamus asper) have been carried out to increase its heating efficiency. Observation was carried out on temperature profile, temperature elevation rate, fuel consumption rate and heating efficiency.Analysis on the charcoal briquettes includes moisture content, volatile substance on 950 C, fixed carbon and calorific value.The experiment revealed that the use of bamboo charcoal briquette of Andong and Petung with density respectively of 0.484 and 0.488 in unmodified traditional anglo give heating efficiency of respectively 16.36 % and 17.4 %. Whereas by increasing the density of bambu charcoal of Andong and Petung to respectively 0.5689 gr/cm3 and 0.5021 gr/cm3 and reducing the ventilation of anglo, the heating efficiebcy can be increased to respectively 40.27 % and 45.06 %. Moreover, the tested bamboo charcoal briquette of Andong has moisture content of 6.83 % (wb),volatile substance at 950 C of 22.71 %, Fixed carbon of 71.15 % and calorific value of 6668 cal/g, whereas the bamboo charcoal briqutte of Petung has moisture content of 4.25 % *wb), volatile substance at 950 C of 25.48 %, fixed carbon of 68.19 % and calorific value of 5018 cal/g.